Sustaining and Sharing Economic Growth in Tanzania - Utz, Robert J. (Washington, DC: World Bank, 2012)
This book is designed to contribute to the government's thinking on how best to translate broad MKUKUTA (the government of Tanzania's National Strategy for Growth and Reduction of Poverty) policy objectives into practical tactics and programs well suited to Tanzania's economic priorities and to the removal of key institutional and infrastructure bottlenecks. The book aims to respond to three fundamental questions: (a) what factors explain Tanzania's recent acceleration in economic growth, (b) how well has the accelerated growth translated into reduced poverty, and (c) what needs to be done to sustain growth that is also pro-poor. This book focuses on three issues that are central to the success of Tanzania's poverty reduction efforts: What factors explain Tanzania's recent acceleration in economic growth? Has the accelerated economic growth translated into reduced poverty? What must be done to sustain economic growth that is pro-poor? The book presents evidence from the macroeconomic, sectoral, firm, and household levels that shed light on these questions. In addition, the book examines the effectiveness of measures that support the poor in efforts to accumulate human and physical capital, which would enhance their prospects of contributing to economic growth. Finally, it is important to mention that this book is a compilation of chapters written by authors from the African Development Bank (Peter Mwanakatwe), COWI Consultants (Kerstin Pfliegner), independent consultancies (Marianne Simonsen and Annabella Skof), and the World Bank (Jean-Eric Aubert, Vandana Chandra, Louise Fox, Henry Gordon, Johannes Hoogeveen, Pooja Kacker, Ying Li, Allister Moon, Philip Mpango, Ravi Ruparel, Anuja Utz, Robert J. Utz, and Michael Wong).